Population Thinking in Architecture - Trummer, Peter (Complexity and Planning, 2012)
This chapter explores how through the use of agent-based modeling (ABM), and its linkage with complexity theory, allows one to create agent-based models for the studying cities from the bottom-up. The ABM paradigm provides a mechanism for understanding the effects of interactions of individuals and through such interactions emergent structures develop, both in the social and physical environment of cities. One such approach is agent-based modelling (ABM) which allows one to simulate the individual actions of diverse agents, measuring the resulting system behaviour and outcomes over time. Animate agents can be considered as agents who move about the systems, such as pedestrians. The ability of agent-based models to describe the behaviour and interactions of a system additionally allows for system dynamics to be directly incorporated into the model. Agent-based simulations provide an opportunity to represent and test social theories which cannot easily be described using mathematical formula.